Viral diseases of cowpea and their control by resistance conferring genes - Hampton, R.; Thottappilly, G.; Rossel, H. (1997)
Cowpea crops are susceptible low more than 20 viral diseases. Some of the most destructive viral pathogens are transmitted from one plant generation to the next through the seed, and thus are generally disseminated to most cowpea-producing regions of the world. Seedborne cowpea viruses, after establishment in plantings as seedborne inoculum, are typically spread within fields by insect vectors (either aphid or beetle species). The most effective control of cowpea viral diseases, universally, has been the development of improved genotypes with resistance to viral infection. The historic productiveness of cowpea breeder-geneticists, describing genes/ resistance to almost every major virus, now provides opportunities to develop multiple resistance to diseases, insect pests, Striga spp., and drought. Although cowpea may lag behind other major food plants in the availability of superior new cultivars with multiple-disease/pest resistance, an extremely valuable base of germplasm exists for much greater development and utilization in the future.